2009
DOI: 10.4315/0362-028x-72.7.1404
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Escherichia coli O157:H7 in Blade-Tenderized Beef Steaks Cooked on a Commercial Open-Flame Gas Grill

Abstract: Beef subprimals were inoculated on the lean side with ca. 4.0 log CFU/g of a cocktail of rifampin-resistant (Rif(r)) Escherichia coli O157:H7 strains and then passed once through a mechanical blade tenderizer with the lean side facing upward. Inoculated subprimals that were not tenderized served as controls. Two core samples were removed from each of three tenderized subprimals and cut into six consecutive segments starting from the inoculated side. A total of six cores were also obtained from control subprima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…In addition, Gill and McGinnis (5) cooked retail whole muscle, nonintact beef from 63 to 68uC and reported that cooking whole muscle, nonintact beef to medium rare would be adequate for reducing aerobic bacteria. Similarly, Luchansky et al (10), using a commercial gas grill to cook E. coli O157:H7inoculated whole muscle, nonintact beef steaks, reported a 2.6 to 4.2 log CFU/g reduction when the meat was cooked between 48.9 and 60uC. The current study supports that cooking brine-injected roast beef to 60uC with a 12-min hold under commercial conditions is an effective method for eliminating internalized E. coli O157:H7.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, Gill and McGinnis (5) cooked retail whole muscle, nonintact beef from 63 to 68uC and reported that cooking whole muscle, nonintact beef to medium rare would be adequate for reducing aerobic bacteria. Similarly, Luchansky et al (10), using a commercial gas grill to cook E. coli O157:H7inoculated whole muscle, nonintact beef steaks, reported a 2.6 to 4.2 log CFU/g reduction when the meat was cooked between 48.9 and 60uC. The current study supports that cooking brine-injected roast beef to 60uC with a 12-min hold under commercial conditions is an effective method for eliminating internalized E. coli O157:H7.…”
Section: Resultssupporting
confidence: 81%
“…Little research has been conducted to streamline this process by examining the efficacy of including antimicrobials directly in the brine solution (11,19,20). Furthermore, thermal processing has been proven to be an effective method of reducing or eliminating internalized pathogens in whole muscle, nonintact beef in experimental settings (10,13). However, the thermal destruction of internalized pathogens needs to be evaluated under simulated commercial conditions for roast beef products.…”
mentioning
confidence: 99%
“…A commercial gas grill (Model XXE-4, Baker's Pride, New Rochelle, NY) was used in this study (Luchansky et al, 2009). Upon use, the gas grill was ignited and the oven was turned on for at least 10 min to allow the flame to stabilize.…”
Section: Gas Grilling Of Beef Steaksmentioning
confidence: 99%
“…However, with this improvement in tenderness, there is a chance that bacteria present on the meat's surface can be transferred to the interior during these processes (Sporing, 1999;Phebus et al, 2000;Sutterfield, 2008). Luchansky et al (2009) concluded that bacterial translocation resulting from blade tenderization occurs primarily in the top portion of the meat, and it is not a food safety concern if the meat is cooked to at least a rare degree of doneness.…”
Section: Introductionmentioning
confidence: 99%